A new criterion to evaluate the machined surface quality of the Nomex® honeycomb materials. (September 2021) - Jaafar, M.; Makich, H.; Nouari, M.
Abstract: The use of sandwich structures based on composite and/or metallic honeycomb core has grown considerably these last years, especially for aeronautic, aerospace, naval and automotive fields. The proposed work deals with the analysis of milling Nomex® honeycomb core that usually generates poor machined surface quality and problems in assembling parts. The performance of milling process and obtained surface quality are strongly influenced by the honeycomb material properties and cutting parameters. The composite nature of the Nomex® paper forming the honeycomb structure, the thin wall thickness and its alveolar shape make the use of conventional parameters of quantifying the surface quality (as roughness) inappropriate. In this study a new method of measurement of the surface quality has been developed. This innovative approach allows simultaneously the identification and quantification of induced machining defects, as well as the evaluation of the performance of the obtained surface. A new quality criterion was then carried out to obtain the best compromise between high surface quality and optimal cutting conditions. This will improve the use of honeycomb materials in sandwich assemblies for industry. Graphical abstract: Unlabelled Image Highlights: Analysis of machining Nomex honeycomb with specific cutting tools Obtained surface quality is strongly influenced by honeycomb material properties and cutting parameters. Identification of a new criterion for the machined honeycomb surface evaluation A new quality criterion makes able to choose the optimal cutting conditions.